Quantitative structural organization of the sclera in chicks after deprivation myopia measured with second harmonic generation microscopy - Bueno, Juan M.; Martínez-Ojeda, Rosa M.; Fernández, Enrique J.; Feldkaemper, Marita (Frontiers in Medicine, 2024)
Visual deprivation causes enhanced eye growth and the development of myopia, which is associated with a change in the arrangement of collagen fibers within the sclera. A second harmonic generation (SHG) microscope has been used to image the collagen fibers of unstained scleral punches from the posterior part of chicken eyes. We aimed to analyze the fibrous scleral tissue and quantify the changes in collagen organization in relation to the extent of induced deprivation myopia. The scleral architecture was assessed with the Radon transform (RT) through the parameter called structural dispersion (SD) that provides an objective tool to quantify the level of organization of the collagen network. We found that final refraction and axial length changes were linearly correlated. However, no significant differences in scleral thickness were found for different amounts of induced myopia. In contrast, a significant correlation between SD and refraction was demonstrated, ranging from a non-organized (in the control sclerae) to a quasi-aligned distribution (with a dominant direction of the fibers, in the sclera of myopic chicks). These findings demonstrate a remodeling process of the scleral collagen associated with myopia progression that can be measured accurately combining SHG imaging microscopy and RT algorithms.